Cardiopulmonary resuscitation duty cycle in out-of-hospital cardiac arrest. (February 2015) - Johnson, Bryce V.; Coult, Jason; Fahrenbruch, Carol; Blackwood, Jennifer; Sherman, Larry; Kudenchuk, Peter; Sayre, Michael; Rea, Thomas
Abstract: Background: Duty cycle is the portion of time spent in compression relative to total time of the compression–decompression cycle. Guidelines recommend a 50% duty cycle based largely on animal investigation. We undertook a descriptive evaluation of duty cycle in human resuscitation, and whether duty cycle correlates with other CPR measures. Methods: We calculated the duty cycle, compression depth, and compression rate during EMS resuscitation of 164 patients with out-of-hospital ventricular fibrillation cardiac arrest. We captured force recordings from a chest accelerometer to measure ten-second CPR epochs that preceded rhythm analysis. Duty cycle was calculated using two methods. Effective compression time (ECT) is the time from beginning to end of compression divided by total period for that compression–decompression cycle. Area duty cycle (ADC) is the ratio of area under the force curve divided by total area of one compression–decompression cycle. We evaluated the compression depth and compression rate according to duty cycle quartiles. Results: There were 369 ten-second epochs among 164 patients. The median duty cycle was 38.8% (SD = 5.5%) using ECT and 32.2% (SD = 4.3%) using ADC. A relatively shorter compression phase (lower duty cycle) was associated with greater compression depth (test for trend <0.05 for ECT and ADC) and slower compression rate (test for trend <0.05 for ADC). Sixty-one of 164 patients (37%) survived to hospital discharge. Conclusions: Duty cycle was below the 50% recommended guideline, and was associated with compression depth and rate. These findings provider rationale to incorporate duty cycle into research aimed at understanding optimal CPR metrics.